Originally, I have (1+Γ) / ($e^{-j\beta z} + Γ*e^{j\beta z}$) = 3/2. I understand I must get rid of the complex number on the denominator, but I do not know how to do this. Please help with this simplification at least.


Rearrange the equation

$$1+Γ = \frac32e^{-j\beta z} + \frac32Γe^{j\beta z}$$

Solve for Γ

$$Γ = \frac{1-\frac32e^{-j\beta z}}{\frac32e^{j\beta z}-1} =\frac{(1-\frac32e^{-j\beta z})(\frac32e^{-j\beta z}-1)}{(\frac32e^{j\beta z}-1)(\frac32e^{-j\beta z}-1)} =-\frac{(\frac32e^{-j\beta z}-1)^2}{\frac94+1}=-\frac{1}{13}(3e^{-j\beta z}-2)^2$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.